ISQGD Distinguished Lecture Series: Fifteen Lectures from December 2025 to April 2026 (Article 008) - ISQGD Editorial Office (ISQGD Bulletin, 2026)
From December 5, 2025 to April 17, 2026, the International Society in Quantization, Geometry, and Dynamics (ISQGD) successfully organized fifteen distinguished lectures under the ISQGD Distinguished Lecture Series. This remarkable sequence of lectures brought together internationally recognized scholars working in diverse areas of mathematics, including quantization, geometry, dynamical systems, harmonic analysis, fractal geometry, operator theory, and related interdisciplinary fields. The series was designed to promote high-level mathematical communication while creating a truly global platform for the exchange of ideas. Through these lectures, ISQGD offered researchers, faculty members, postdoctoral scholars, graduate students, and enthusiastic learners around the world an opportunity to engage with contemporary mathematical research in an accessible, professional, and interactive setting. The successful organization of these fifteen lectures within a relatively short period reflects the strong academic vision of ISQGD and its commitment to advancing mathematics from broad educational outreach to higher research. It also demonstrates the society’s dedication to fostering international collaboration, scholarly excellence, and the long-term dissemination of mathematical knowledge. An especially valuable feature of this lecture series is its permanent public accessibility. All lectures are available for public viewing through the ISQGD YouTube Channel, making this growing collection a lasting academic resource for the global mathematical community. In addition, all Distinguished Lectures can be conveniently explored through the official archive page: ISQGD Archive, where detailed records, including lecture titles and related information, are systematically organized. The following distinguished speakers delivered lectures in the series: ISQGD–DL15 — Sascha Troscheit — April 17, 2026 ISQGD–DL14 — Wuchen Li — April 3, 2026 ISQGD–DL13 — Lars Olsen — March 27, 2026 ISQGD–DL12 — Zhiqiang Wang — March 13, 2026 ISQGD–DL11 — Kenneth M. Golden — March 6, 2026 ISQGD–DL10 — Kenneth Falconer — February 27, 2026 ISQGD–DL09 — Christian Wolf — February 20, 2026 ISQGD–DL08 — Károly Simon — February 13, 2026 ISQGD–DL07 — William O'Regan — February 6, 2026 ISQGD–DL06 — Patrick D. Shipman — January 30, 2026 ISQGD–DL05 — Jonathan Fraser — January 23, 2026 ISQGD–DL04 — Stefano Galatolo — January 16, 2026 ISQGD–DL03 — Balázs Bárány — December 19, 2025 ISQGD–DL02 — Peter Massopust — December 12, 2025 ISQGD–DL01 — Palle Jorgensen — December 5, 2025 Together, these lectures form an important part of the early academic record of ISQGD and highlight the society’s emerging role as a vibrant international center for mathematical research, communication, and collaboration. With this continuing momentum, ISQGD looks forward to expanding the Distinguished Lecture Series further and strengthening its position as one of the leading global organizations dedicated to mathematics and interdisciplinary innovation.